Knockdown of the Expression of Two Trehalase Genes with RNAi Disrupts the Trehalose and Chitin Metabolism Pathways in the Oriental Armyworm, Mythimna separata - Hongjia Yang; Yixiao Wang; Weijia Zhang; Xinxin Zhang; Sibo Wang; Mengyao Cui; Xiaohui Zhao; Dong Fan; Changchun Dai (Insects, 2024)
Trehalose is an important carbohydrate substance in insect hemolymph. Chitin is the main component of cuticle and peritrophic matrix in insects. Trehalase (Tre) catalyzes the decomposition of trehalose. Few studies of trehalase in lepidopteran insects have been conducted. Here, the functions of soluble Tre (Tre1) and membrane-bound Tre (Tre2) in the growth and development of Mythimna separata were investigated. We cloned and identified Tre1 and Tre2 cDNA sequences in M. separata. Analysis expression revealed that MsTre1 and MsTre2 were highly expressed in midgut and integument, respectively. The expression of MsTre1 and MsTre2 was highest in the pupal stage. We used RNA interference (RNAi) to inhibit Tre expression in M. separata larvae. Injection of dsMsTre1 or dsMsTre2 resulted in abnormal phenotypes and impeded normal molting. Silencing of MsTre1 and MsTre2 resulted in significant changes in the expression of genes in the trehalose and chitin metabolism pathways, significantly increased the trehalose and glycogen content, and significantly decreased MsTre1 and MsTre2 activity, the glucose content, and the chitin content in midgut and integument. Silencing of MsTre1 slowed larval molting, and the new cuticle was significantly thinner. These results indicate that RNAi of Tre may be useful for control strategies against M. separata.